Berberine-Loaded Biomimetic Nanoparticles Attenuate Inflammation of Experimental Allergic Asthma via Enhancing IL-12 Expression - Jin, Hua; Li, Jiale; Zhang, Miaoyuan; Luo, Renxing; Lu, Peishan; Zhang, Wenting; Zhang, Junai; Pi, Jiang; Zheng, Weixin; Mai, Zesen; Ding, Xiaowen; Liu, Xinguang; et al. (Frontiers in Pharmacology, 2021)
Asthma is one of the most common chronic pulmonary disorders, affecting more than 330 million people worldwide. Unfortunately, there are still no specific treatments for asthma so far. Therefore, it is very important to develop effective therapeutics and medicines to deal with this intractable disease. Berberine has fabulous anti-inflammatory and anti-bacterial effects, while its low water solubility and bioavailability greatly limit its curative efficiency. To improve the nasal mucosa absorption of poorly water-soluble drugs, such as Berberine, we developed a platelet membrane coated nanoparticle system (PM@Ber-NPs) for targeted delivery of Berberine to the inflammatory lungs. In vivo, PM@Ber-NPs exhibited enhanced targeting retention in the inflammatory lungs compared with free Berberine. In a mouse model of HDM-induced asthma, PM@Ber-NPs markedly inhibited lung inflammation as evidenced by reduced inflammatory cells and inflammatory cytokines in the lung compared with free Berberine. Collectively, our study demonstrated the inhibitory actions of nasally delivery nano-medicines on HDM-induced asthma, primarily through regulating Th1/Th2 balance by enhancing IL-12 expression which could potentially reduce lung inflammation.